Rancang Bangun Aplikasi Pengenalan Bahasa Isyarat “Peduli Penyandang Disabilitas” Berbasis Android Menggunakan Metode Agile - Firnanda Gunawan; Resti Amalia (CV. Multi Kreasi Media, 2024)
Communication between humans is very important in everyday life. In communication, a communication model is needed. In social communication, humans always use language to communicate. But not everyone in this world can communicate perfectly, one of them is a person with special needs. One that can be used is sign language. Sign language itself has a limited range of uses. In contrast to the Special Schools (SLB) environment, where the use of sign language has always been a priority language, in the life of the community itself each sign language is foreign, even though there are several deaf people around them, so there are still many people who do not know or understand the sign language conveyed by interlocutor. This raises the need for learning facilities to learn this sign language easily. Because sign language is a means of communication for deaf people with the people around them. Because there is still a lack of sign language learning media that is easily accessible to all people, this application was made to help people who want to learn sign language. This application is designed using the agile extreme programming method to increase client satisfaction and make the system development faster.